Addressing Governance at the Center of Higher Education Reforms in Armenia - World Bank (Washington, DC, 2014)
Since joining the Bologna process in 2005, the Armenian government and higher education institutions have made significant progress in reforming the higher education system. Despite reforms, the public perception of higher education governance and management is poor. Reasons for the poor public perception of higher education governance are primarily embedded in system-wide factors. Recent research has identified a governance structure and regulatory framework as key to the development of overall higher education systems. The study finds that underperformance of the higher education system is associated with a legal framework that lacks coherence and the entire system lacks capacity to effectively exercise autonomy and accountability.